Making addiction, making gender: A feminist performativity analysis of Kakavas v Crown Melbourne Limited - Seear, Kate (Taylor & Francis Australasia, 2015)
This paper examines the landmark 2013 judgment of the Australian High Court in Kakavas v Crown Melbourne Limited. This case focused on the activities of Australian businessman Harry Kakavas, a regular gambler at Melbourne’s Crown casino. Kakavas argued that he was a pathological gambler unconscionably exploited by the casino. Using feminist and queer performativity theory, as well as a science and technology studies (STS) approach to the law, I explore how the court constituted gambling addiction and gender in the case. Via John Law’s notion of ‘collateral realities’, I also examine the way that legal judgments ostensibly dealing with one object can simultaneously materialise other realities, a point with relevance well beyond the present example. I conclude with reflections on the implications of this analysis for law, policy and practice in the study of addiction and gender.